The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1016/j.fertnstert.2021.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Maternal body mass index is not associated with increased rates of maternal embryonic aneuploidy

Abstract: Objective: To evaluate the relationship between maternal body mass index (BMI) and embryonic aneuploidy of maternal origin. Design: Retrospective cohort analysis. Setting: University hospital-based reproductive center. Patients: Maternal origin of aneuploidy was available for 453 cycles and 1,717 embryos. Interventions: Data regarding BMI were collected before egg retrieval. Comparison groups included underweight (BMI, <18.5 kg/m 2 ), normal weight (BMI, 18.5-24.9 kg/m 2 ), overweight (BMI, 25-29.9 kg/m 2 ), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The number or percentage of aneuploid, mosaic, or euploid fetuses was not really related to BMI [9]. 3.…”
Section: Bellver Et Al Stated That Obese and Normal-weightmentioning
confidence: 88%
“…The number or percentage of aneuploid, mosaic, or euploid fetuses was not really related to BMI [9]. 3.…”
Section: Bellver Et Al Stated That Obese and Normal-weightmentioning
confidence: 88%
“…Maternal BMI was not associated with higher rates of preimplantation embryonic aneuploidy. 18 19 In addition, paternal obesity was also not found to be associated with higher rates of preimplantation embryonic aneuploidy. 20…”
Section: Pathophysiology Between Obesity and Miscarriagementioning
confidence: 88%
“…Maternal BMI was not associated with higher rates of preimplantation embryonic aneuploidy. 18,19 In addition, paternal obesity was also not found to be associated with higher rates of preimplantation embryonic aneuploidy. 20 In support of these findings, several other clinical, human studies have evaluated products of conception after an early pregnancy loss and come to the same conclusion.…”
Section: Embryomentioning
confidence: 93%
“…To emphasize the controversy, in a previous report on ART, BMI was associated with embryogenesis 2 ; however, no effect was reported 3 . One previous study reported no difference in the ratio of chromosomal aneuploidy between women with and without obesity in preimplantation genetic testing for aneuploidy 4 , 5 . In addition, obesity in women has been associated with decreased pregnancy or live birth rates 6 11 , although some reports suggest no such association 2 , 12 14 .…”
mentioning
confidence: 92%